1990
DOI: 10.2135/cropsci1990.0011183x003000060034x
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration in Cereal Tissue Culture: a Review

Abstract: This review examines the literature on successful establishment of regenerable cell cultures in the economically important cereal crops. Some of the major trends and strategies for the establishment of in vitro cultures that express totipotency are discussed as well as current approaches. It is apparent that in cereal tissue culture, not all cells express totipotency. Generally the auxin 2,4‐dichlorophenoxyacetic acid (2,4‐D) is critical for the production of regenerable callus; however, the addition of cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
104
2
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(113 citation statements)
references
References 0 publications
6
104
2
1
Order By: Relevance
“…While low concentrations of BAP favored the development of shoot buds from the pre-existing meristems (Shiva Prakash et al 1994;Ignacimuthu et al 1997). However, higher number of viable plants were regenerated on KIN medium in several cereal crops (Bhaskaran and Smith 1990). In contrast, the present studies demonstrated that 5.0 mg L −1 KIN had low shoot bud regeneration compared to 2.5 mg L −1 BAP and 0.5 mg L −1 TDZ (Fig.…”
Section: Shoot Bud Regenerationcontrasting
confidence: 62%
“…While low concentrations of BAP favored the development of shoot buds from the pre-existing meristems (Shiva Prakash et al 1994;Ignacimuthu et al 1997). However, higher number of viable plants were regenerated on KIN medium in several cereal crops (Bhaskaran and Smith 1990). In contrast, the present studies demonstrated that 5.0 mg L −1 KIN had low shoot bud regeneration compared to 2.5 mg L −1 BAP and 0.5 mg L −1 TDZ (Fig.…”
Section: Shoot Bud Regenerationcontrasting
confidence: 62%
“…Both plumule and radicle tissues are juvenile tissues that contain meristematic cells that are main targets of plant growth regulator action (Bhaskaran & Smith 1990;Feher 2006;Vasil 1988). Moreover, external supply of 2,4-D accelerated induction of calli on these explants such that the developmental responses were highly dependent on endogenous and exogenous hormonal concentrations in agreement with Feher (2006).…”
Section: Discussionmentioning
confidence: 95%
“…According to Jimenez (2001); Chaudhury and Qu (2000), in order to determine the induction and expression of the growth and development of young plants, a certain ratio of endogenous and exogenous hormones is required. The effectiveness of exogenous growth regulators depends on the concentration of endogenous hormones (Bhaskaran and Smith, 1990). Then according to Cavusoglu et al (2008) triacontanol is very effective in trunk diameter, which is able to increase the width of the vascular vessels, xylem width, and the width of the phloem.…”
Section: Discussionmentioning
confidence: 99%